Pertanggungjawaban Pidana bagi Pembuat Drug Design dalam Perspektif Hukum Narkotika - Aulia Rahma Sari (Jurist-Diction, 2025)
The proliferation of technology has fueled the rise of drug abuse, giving rise to new modus operandi such as "Drug Design," where novel chemical compounds are synthesized to mimic the effects of illicit drugs without falling under existing drug laws. These "designer drugs," like PCC Pills," have caused severe mental health issues, fatalities, and pose a significant challenge to law enforcement due to their rapid molecular modifications. To address this emerging legal issue, this paper employs a normative legal research methodology to analyze the associated legal implications. Drug Design, stemming from the illicit practices of clandestine chemists, complicates law enforcement efforts due to the difficulty in classifying these novel substances. Collaboration between law enforcement agencies and chemists is crucial to determine appropriate legal sanctions. Despite regulatory efforts, the challenges of regulating and enforcing against Drug Design remain substantial, necessitating a cautious approach to both drug law enforcement and the regulation of emerging substances.